Sex differences in clinical characteristics and 1-year outcomes of young ischemic stroke patients in East China - Geng C; Lin Y; Tang Q; Tang Y; Wang X; Zhou JS; Yang J; Zheng D; Zhang YD (Dove Medical Press, 2018)
Cong Geng,1,2,* Yapeng Lin,3,* Qin Tang,3 Yifang Tang,3 Xiaoqing Wang,3 Jun-shan Zhou,1 Jie Yang,3 Danni Zheng,4,5 Ying-dong Zhang1 For the Nanjing First Hospital Stroke Registry Investigators 1Department of Neurology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu 210006, China; 2Department of Emergency, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu 215000, China; 3Department of Neurology, The First Affiliated Hospital of Chengdu Medical College, Xindu, Chengdu 610500, China; 4Centre for Big Data Research in Health, Faculty of Medicine, University of New South Wales, Sydney 2033, NSW, Australia; 5The George Institute for Global Health, Faculty of Medicine, University of New South Wales, Sydney 2033, NSW, Australia *These authors contributed equally to this work Background: Data concerning sex differences in clinical characteristics and outcomes of young ischemic stroke (IS) patients in Eastern China are scarce. Understanding sex differences in clinical characteristics and long-term outcomes of young IS patients might provide valuable evidence for designing preventative measures and therapeutic interventions. Methods: The study included 228 acute IS patients aged up to 50 years recruited in the prospective Nanjing First Hospital Stroke Registry over a 5-year period. Univariable and multivariable logistic regression analyses were performed to determine whether there were sex differences in clinical characteristics and outcomes of young IS patients. Results: Admission systolic blood pressure (130.12±24.3 vs 137.96±24.3 mmHg, P=0.005) of women was significantly lower than that of men. Logistic regression showed that young women had poorer outcomes defined as having modified Rankin Scale score of 3–6 at 12 months after the adjustment for history of prior stroke, NIHSS score, and complication of pneumonia (adjusted OR: 3.45; 95% CI: 1.43–8.32). Conclusion: Our study indicates that there may be significant differences in clinical characteristics between young women and men with acute IS in East China. Young women were more likely to be dead or dependent at 12 months after stroke onset. More attention should be paid to young women’s IS prevention and management in East China. Keywords: sex differences, young ischemic stroke, clinical characteristics, outcomes